PENGARUH PELATIHAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi Pada Karyawan Hotel Megaland Solo) - Citraningtyas, Nuridha; Djastuti, Indi (Diponegoro Journal of Management, 2017)
Employee’s performance is one of the important factors for a company to reach their goals. Aside of being the factor to reach the company’s goals, employee’s performance also included as a way to measure the quality of the human resources in a company. Some of the factors which might caused an impact to employee’s performance are training, work environment and work satisfaction. The purpose of this research is to get to know if there is any impacts from training and work environment to employee’s performance with work satisfaction as the intervening.This research was done in Hotel Megaland Solo with total sample of 68 respondents who are actually the employees of the hotel. The method of data analysis which used in this research was the double regression method.The result of this research showed that training, work environment and work satisfaction variables have positive and significant impacts on employee’s performance,